The Effect of Resistance Strength Training on Muscle Cross Education: A Meta analysis - Hao Dong, Yuan; Luo, Jiong (Quality in Sport, 2025)
Introduction: At present, a large number of studies have found that the phenomenon of cross transfer has achieved significant research results in sports training, rehabilitation therapy, and influencing mechanisms. Cross training refers to increasing muscle strength on the training side, while there is also a significant increase in muscle strength on the untrained homologous side. The main purpose of this review is to explore the impact mechanism of cross transfer phenomenon and summarize the optimal training methods and rehabilitation methods for cross transfer phenomenon. Aim of the study: Using meta-analysis method to systematically evaluate the effects of cross training (also known as cross education) on upper and lower limb muscle strength in different age groups and compare the training results. Material and methods: The system searched databases such as Wanfang Digital Resource Database, China National Knowledge Infrastructure Database, EBSCOhost, PubMed, Web of Science, and Cochrane Library from the default start time to December 2024. Two evaluators independently screened research literature on resistance strength training improving upper and lower limb muscle strength and hypertrophy in various age groups based on inclusion and exclusion criteria. Revmen 5.3 was used to evaluate all included literature and analyze their data. Result: 1)After 4 rounds of exclusion, 7 articles were finally included with a total sample size of 257 people; 2) Cross education intervention under resistance strength training can significantly enhance the strength of the quadriceps muscle in adults, with better results than the control group. The combined effect size is SMD=8.03, 95% CI:- 1.32，17.37， P＜0.01， 3) The degree to which cross education intervention enhances the strength of the gastrocnemius and wrist extensor muscles under resistance strength training is similar. The combined effect quantities are: SMD＝0.17，95% CI：-2.28，2.62，P≥0.01； SMD＝-0.39，95% CI：-3.02，2.25，P≥0.01； SMD=0.20, 95% CI: -0.81, 1.21, P ≥ 0.01 Conclusion: Cross education intervention under resistance strength training can significantly improve quadriceps strength and promote muscle hypertrophy in adults; The effect of cross education intervention under resistance force on promoting the strength and hypertrophy of the gastrocnemius muscle and wrist extensor muscle is similar.